2020
DOI: 10.3390/jof6030103
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Interaction between Isavuconazole and Tacrolimus, Cyclosporin A, or Sirolimus against Aspergillus Species

Abstract: The interaction of isavuconazole with immunosuppressors (tacrolimus, cyclosporin A, or sirolimus) against 30 Aspergillus isolates belonging to the most common species responsible for invasive aspergillosis in humans (Aspergillus flavus, Aspergillus fumigatus, Aspergillus nidulans, Aspergillus niger, and Aspergillus terreus) was evaluated in vitro by a microdilution checkerboard technique based on the EUCAST reference method for antifungal susceptibility testing. The interpretation of the results was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Already prior to the COVID-19 pandemic repurposing of drugs had become trendy. Repurposed drugs have shown activity against bacteria 29 , yeasts 29,30 , and filamentous fungi [31][32][33][34] . Colistin is a drug of last resort with activity against multidrug-resistant gram-negative bacteria such as Pseudomonas aeruginosa, Klebsiella pneumoniae, or Acinetobacter baumanii 35 ; but colistin has also shown to damage the cell membrane of C. albicans 17 , which could make it an interesting partner in combination therapy against multidrug-resistant C. auris infections.…”
Section: Discussionmentioning
confidence: 99%
“…Already prior to the COVID-19 pandemic repurposing of drugs had become trendy. Repurposed drugs have shown activity against bacteria 29 , yeasts 29,30 , and filamentous fungi [31][32][33][34] . Colistin is a drug of last resort with activity against multidrug-resistant gram-negative bacteria such as Pseudomonas aeruginosa, Klebsiella pneumoniae, or Acinetobacter baumanii 35 ; but colistin has also shown to damage the cell membrane of C. albicans 17 , which could make it an interesting partner in combination therapy against multidrug-resistant C. auris infections.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports demonstrated that spectrophotometric reading is a good alternative for Aspergillus spp. [ 33 , 34 , 35 ]. Incorporation of spectrophotometric reading leads to more objective MIC determination and automation of the process.…”
Section: Discussionmentioning
confidence: 99%
“… Kubiça et al ( 2016 ) Aspergillus spp. 0.25–16 Mice CAS High and Washburn ( 1997 ); Steinbach et al ( 2004 ); Kubiça et al ( 2016 ); Schwarz and Dannaoui ( 2020 ) Fusarium spp. 1–40 - CAS Shalit et al ( 2009 ) C. albicans No effects.…”
Section: Immunosuppressantsmentioning
confidence: 99%
“… 8 ISA Schwarz et al ( 2019 ) Phycomyces blakesleeanus 6.3-200 - CAS, ISA Bastidas et al ( 2012 ) Aspergillus spp. 16 Mice ISA High and Washburn ( 1997 ); Kontoyiannis et al ( 2003 ); Schwarz and Dannaoui ( 2020 ) Mycophenolic acid C. neoformans 30 Nematode AmB Disrupts de novo GTP biosynthesis. Morrow et al ( 2012 ); Banerjee et al ( 2014 ) C. albicans 0.25 - - Köhler et al ( 2005 ) Mizoribine C. albicans - - - Disrupt de novo GTP biosynthesis.…”
Section: Immunosuppressantsmentioning
confidence: 99%